The effect of 8-week Zumba® fitness on body composition of turkish womens - Güçlüöver, Aziz (Progress in Nutrition, 2020)
The aim of this study is to evaluate the effect of 8-week zumba fitness on body composition of Turkish women between the ages of 18-35. The sample of the study consists of 28 (n = 14 experimental group and n = 14 control group) women who are between the ages of 18-35 and living in the city centre of Kırıkkale. The women in the experimental group participated in the zumba fitness which lasted about 60 minutes 3 days a week for 8 weeks. The women in the control group continued their daily life. Body composition of the participants in both experimental and control groups was determined by Bioelectric Impedance Analysis Method before and after 8 week zumba fitness. The data obtained from applications to determine body composition were evaluated in SPSS 25.0 package program with 95% confidence interval and 0.05 significance level. In statistical analyses, statistically significant difference has been observed in the mean values obtained from the applications of pre-test and post-test regarding variables of BMI (kg/cm2), body fat percentage (% fat), body fat mass (kg), lean body mass (kg), right leg fat percentage (% fat), right leg fat mass (kg) of the women in the experimental group (p<0.05). Within the lights of the findings obtained in the study, it has been concluded that the 8-week zumba fitness caused a decrease in body weight, body fat percentage and BMI values of Turkish women between the ages of 18-35. In the regional body analysis done in the study, it has been understood that the effect of the zumba fitness program was on the lower extremity.